Genomic insight into Campylobacter jejuni isolated from commercial turkey flocks in Germany using whole-genome sequencing analysis - El-Adawy, Hosny; Hotzel, Helmut; García-Soto, Silvia; Tomaso, Herbert; Hafez, Hafez M.; Schwarz, Stefan; Neubauer, Heinrich; Linde, Jörg (Frontiers in Veterinary Science, 2023)
Campylobacter jejuni is a zoonotic bacterium of public health significance. The present investigation was designed to assess the epidemiology and genetic heterogenicity of Campylobacter jejuni isolated from commercial turkey flocks in Germany using whole-genome sequencing. The Illumina MiSeq® technology was used to sequence 66 Campylobacter jejuni isolates obtained between 2010 and 2011 from commercial meat turkey flocks located in ten German federal states. Phenotypic antimicrobial resistance was determined. Phylogeny, resistome, plasmidome and virulome profiles were analysed using whole-genome sequencing data. Genetic resistance markers were identified with bioinformatics tools (AMRFinder, ResFinder, NCBI and ABRicate) and compared with the phenotypic antimicrobial resistance. The isolates were assigned to 28 different sequence types and 11 clonal complexes. The average pairwise single nucleotide-polymorphisms distance of 14.585 SNPs (range: 0 - 26.540 SNPs) showed a high genetic diversity among the isolates. In the Campylobacter jejuni isolates, 30 virulence-associated genes were identified. Most of the isolates harboured the genes flaA (83.3%) and flaB (78.8%). The wlaN gene involved in the Guillain–Barré syndrome was found in nine (13.6%) isolates. The genes for resistance to ampicillin (blaOXA), tetracycline (tet(O)), neomycin (aph(3')-IIIa), streptomycin (aadE) and streptothricin (sat4) were detected in isolated C. jejuni using WGS. A gene cluster comprising the genes sat4, aph(3')-IIIa and aadE was present in six isolates. The single point mutation T86I in the housekeeping gene gyrA conferring resistance to quinolones was retrieved in 93.6% of phenotypically fluoroquinolone-resistant isolates. Five phenotypically erythromycin-susceptible isolates carried the mutation A103V in the gene for the ribosomal protein L22 inferring macrolide resistance. A variety of 13 known β-lactam resistance genes (blaOXA variants) was detected in 58 C. jejuni isolates. Out of 66 sequenced isolates, 28 (42.4%) carried plasmids. Six isolates harbored a pTet plasmid which carries the tet(O) gene. This study highlighted the potential of whole-genome sequencing for improving routine surveillance of C. jejuni. Whole-genome sequencing can predict antimicrobial resistance with a high degree of accuracy. However, resistance gene databases need curation and updates to avoid inaccuracy when using WGS-based analysis pipelines for AMR detection.